1988
DOI: 10.1128/aac.32.6.936
|View full text |Cite
|
Sign up to set email alerts
|

No cytogenetic effects of quinolone treatment in humans

Abstract: Cytogenetic effects of ciprofloxacin (500 to 2,000 mg daily) and ofloxacin (200 mg daily) were studied in lymphocytes from 31 patients treated for 1 to 10 weeks. Blood samples for cytogenetic analysis were taken before the start of treatment from all patients, after 1 week from 25 patients, and after 2, 4, 6, and 10 weeks from six patients. No chromosome-damaging effect could be demonstrated in any treatment group. The mean aberration yields for each cytogenetic parameter studied and the total number of aberra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…These findings suggest the possibility that these new quinolones may induce genotoxic effects in humans. In clinical experience, however, ciprofloxacin and ofloxacin have failed to induce chromosomal aberrations in peripheral lymphocytes in Phase I volunteers and patients (Shimada et al, 1984;Mitelman et al, 1988). Results from the in vitro and in vivo cytogenetic studies suggest that the potency of these drugs in the induction of chromosomal aberrations may in part be due to the affinity of each quinolone for topoisomerase II.…”
Section: Eukaryotic Systemsmentioning
confidence: 94%
“…These findings suggest the possibility that these new quinolones may induce genotoxic effects in humans. In clinical experience, however, ciprofloxacin and ofloxacin have failed to induce chromosomal aberrations in peripheral lymphocytes in Phase I volunteers and patients (Shimada et al, 1984;Mitelman et al, 1988). Results from the in vitro and in vivo cytogenetic studies suggest that the potency of these drugs in the induction of chromosomal aberrations may in part be due to the affinity of each quinolone for topoisomerase II.…”
Section: Eukaryotic Systemsmentioning
confidence: 94%
“…There is currently a good deal of debate in the literature concerning the interpretation of positive in vitro genotoxicity results observed in a single test system, because of the finding that quinolones do not induce the same responses in in vivo tests (9,36,39). McQueen and Williams (36) found that norfloxacin, ofloxacin, pefloxacin, and ciprofloxacin induced DNA breakage and repair in the in vitro rat hepatocyte assay at levels between 300 and 500 p,g/ml.…”
Section: Correlations Of In Vivo Effects With In Vitro Genotoxicity Tmentioning
confidence: 99%
“…Quinolones have been reported to affect eukaryotic cells in vitro by inducing unscheduled DNA synthesis, DNA strand breakage, inhibition of cell growth, and inhibition of immunoglobulin secretion in human lymphocytes (2,6,13,23). The in vivo effects of quinolones on eukaryotic cells are not as well documented and are usually negative (21,23). However, abnormal bone marrow cells were observed for mice given five daily parenteral doses of the quinolone CP-67,015 at 500 mg/kg of body weight per day (11).…”
Section: Mutagenicity Of Quinolones In the Amesmentioning
confidence: 99%